2015
DOI: 10.1093/nar/gkv1162
|View full text |Cite
|
Sign up to set email alerts
|

Binding of 14-3-3 reader proteins to phosphorylated DNMT1 facilitates aberrant DNA methylation and gene expression

Abstract: Mammalian DNA (cytosine-5) methyltransferase 1 (DNMT1) is essential for maintenance methylation. Phosphorylation of Ser143 (pSer143) stabilizes DNMT1 during DNA replication. Here, we show 14-3-3 is a reader protein of DNMT1pSer143. In mammalian cells 14-3-3 colocalizes and binds DNMT1pSer143 post-DNA replication. The level of DNMT1pSer143 increased with overexpression of 14-3-3 and decreased by its depletion. Binding of 14-3-3 proteins with DNMT1pSer143 resulted in inhibition of DNA methylation activity in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
3
11
0
3
Order By: Relevance
“…We observed a strong negative correlation between DNAJA4 gene methylation and expression in stomach adenocarcinoma, which suggested that methylation of DNAJA4 may suppress gene expression. This is consistent with reports that DNAJA4 expression is strongly influenced by its methylation status [58]. Our data also revealed that patients with low DNAJA4 expression had poorer survival outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…We observed a strong negative correlation between DNAJA4 gene methylation and expression in stomach adenocarcinoma, which suggested that methylation of DNAJA4 may suppress gene expression. This is consistent with reports that DNAJA4 expression is strongly influenced by its methylation status [58]. Our data also revealed that patients with low DNAJA4 expression had poorer survival outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…The S143 of DNMT1 is phosphorylated by AKT1, which leads to the stabilization of the methyltransferase ( 99 ). Recently, a specific 14-3-3 family reader protein for this modification was identified ( 100 ). It binds to the phosphorylated DNMT1, leading to the inhibition of DNMT1 activity in vitro and in cells, and subsequent aberrant DNA hypomethylation ( 100 ).…”
Section: Structure Mechanism and Regulation Of Dnmt1mentioning
confidence: 99%
“…Recently, a specific 14-3-3 family reader protein for this modification was identified ( 100 ). It binds to the phosphorylated DNMT1, leading to the inhibition of DNMT1 activity in vitro and in cells, and subsequent aberrant DNA hypomethylation ( 100 ). Finally, phosphorylation of DNMT1 by protein kinase C (PKC) has been reported, but the target sites have not yet been identified ( 101 ).…”
Section: Structure Mechanism and Regulation Of Dnmt1mentioning
confidence: 99%
“…S3a, b). 7 Importantly, we observed enriched co-localization of TET2 and nuclear 14-3-3 proteins after treatment with an AMPK activator, A769662 (Supplementary information, Fig. S3b, c).…”
Section: Dear Editormentioning
confidence: 85%